Habitual Communication - Konstantinos Ioannidis (Tinbergen Institute, 2022)
Many everyday activities are habitual. Among the most common human activities is communication. If people primarily communicate in a common-interests environment, they may form habits of truth-telling and believing messages. If they primarily communicate in a conflicting-interests environment, they may form habits of lying and mistrusting mes- sages. We provide experimental evidence that habits affect strategic communication in an unfamiliar environment. Additionally, we contrast two mechanisms through which habits operate, preference formation and inattention. By varying the frequency of communicating in the unfamiliar environment, we find an effect only when the unfamiliar environment oc- curs rarely. Our results favor inattention as preference formation would predict an effect irrespective of the frequency of the new environment. Analysis of individual decisions sheds further light on the mechanisms. Our findings highlight the importance of accounting for habits, especially when studying human behavior in infrequent situations.
Keywords: D91; C92; D01; D83; 330; Habits; Strategic information transmission; Communication; Experiment